2015
DOI: 10.1007/s10502-015-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

Digital curation beyond the “wild frontier”: a pragmatic approach

Abstract: This paper advocates the necessity of developing a pragmatic alternative to the dominant custodial theorization of digital curation as an ''umbrella concept for digital preservation, data curation, electronic records, and digital asset management''. Starting from a historical account and an examination of prevalent definitions, it points to the current dependence of digital curation on a prescriptive approach rooted in its cognate field of digital preservation, aiming to serve the needs of professional steward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…As for the second subsection that seek to evaluate the content provided forth by the E-GDH system, it was reported ( Figure 6) that the content provided on this website was suitable for use by people of all ages as majority of the target respondents either strongly agreed (5) or agreed (8). The question item that asked if it was easy to understand the content on the E-GDH website showed that the content was easily understood as majority of the respondents either strongly agreed (8) or agreed (7) with the question item.…”
Section: Discussionmentioning
confidence: 99%
“…As for the second subsection that seek to evaluate the content provided forth by the E-GDH system, it was reported ( Figure 6) that the content provided on this website was suitable for use by people of all ages as majority of the target respondents either strongly agreed (5) or agreed (8). The question item that asked if it was easy to understand the content on the E-GDH website showed that the content was easily understood as majority of the respondents either strongly agreed (8) or agreed (7) with the question item.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that many issues hindering innovation are challenges also in digitizing cultural heritage [11,19,22]. For example, project management issues, such as understanding the complexity of museum documentation, its digitization projects and evaluation of the completed projects, are significant factors also in museums [23,24]. Digitization puts new requirements to the skills and competencies of its employees [25,26].…”
Section: Background and Related Research On Museums And Ismentioning
confidence: 99%
“…Although some of these films are available to view online through other platforms such as YouTube and Facebook, the creation of the digital archive saw, for the first time, the content being collated together in one place to convey stories from the area through the medium of moving image and other archival materials. The design of a platform for the purposes of digital curation required careful consideration to ensure that it accommodated formats effectively, both those created natively on digital platforms, as well as surrogate materials produced as a result of digitisation from analogue and physical formats (Dallas, 2016). In creating this community archive, the importance of these film artefacts as vehicles for the preservation and celebration of intangible cultural heritage is championed, allowing them to exist within a space which conveys stories and social histories unique to the North-East corner of Scotland.…”
Section: Introductionmentioning
confidence: 99%